Intercultural Europe: Cultural Diversity in the EU and the Debate on a Common European Cultural Identity - Muñoz, Jordi-Jesús (Papeles de Europa, 2017)
The aim of the work is to approach the complex cultural system of the European Union through the analysis of cultural diversity within the EU and the existence of a possible common European cultural identity. This paper attempts to promote the debate on intercultural dialogue in the European Union and the actions undertaken by the European institutions to promote a common cultural identity based on plurality and diversity.